Biomass burning events measured by lidars in EARLINET. Part II. Results and discussions, - Adam, Mariana (2020)
Biomass burning events are analysed using the European Aerosol Research Lidar Network database for atmospheric profiling of aerosols by lidars. Atmospheric profiles containing forest fires layers were identified in data collected by fourteen stations during 2008–2017. The data ranged from complete data sets (particle backscatter coefficient, extinction coefficient and linear depolarization ratio) to single profiles (particle backscatter coefficient). The data analysis methodology was described in Part I (Biomass burning events measured by lidars in EARLINET. Part I. Data analysis methodology, under discussions to ACP, the EARLINET special issue). The results are analysed by means of intensive parameters in three directions: (I) common biomass burning source (fire) recorded by at least two stations, (II) long range transport of smoke particles from North America (here, we divided the events into "pure North America" and "mixed"-North America and local) smoke groups, and (III) analysis of smoke particles over four geographical regions (SE Europe, NE Europe, Central Europe and SW Europe). Five events were found for case (I), while 24 events were determined for case (II). A statistical analysis over the four geographical regions considered revealed that smoke originated from different regions. The smoke detected in the Central Europe region (Cabauw, Leipzig, and Hohenpeißenberg) was mostly brought over from North America (87 % of the fires), by long range transport. The smoke in the South West region (Barcelona, Evora, and Granada) came mostly from the Iberian Peninsula and North Africa, the long-range transport from North America accounting for only 9 % here. The smoke in the North Europe region (Belsk, Minsk, and Warsaw) originated mostly in East Europe (Ukraine and Russia), and had a 31 % contribution from smoke by long-range transport from North America. For the South East region (Athens, Bucharest, Potenza, Sofia, Thessaloniki) the origin of the smoke was mostly located in SE Europe (only 3 % from North America). Specific features for the lidar-derived intensive parameters based on smoke continental origin were determined for each region. Based on the whole dataset, the following signatures were observed: (i) the colour ratio of the lidar ratio and the backscatter Ångström exponent increase with travel time, while the extinction Ångström exponent and the colour ratio of the particle depolarization ratio decrease; (ii) an increase of the colour ratio of the particle depolarization ratio corresponds to both a decrease of the colour ratio of the lidar ratios and an increase of the extinction Ångström exponent; (iii) the measured smoke originating from all continental regions is characterized in average as aged smoke, except for a few cases; (iv) in general, the local smoke shows a smaller lidar ratio while the long range transported smoke shows a higher lidar ratio; and (v) the depolarization is smaller for long range transported smoke. A complete characterization of the smoke particles type (either fresh or aged) is presented for each of the four geographical regions versus different continental source regions.